ANALISIS DAMPAK IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING (ERP) TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL BUMN DALAM PELAPORAN KEUANGAN DI INDONESIA - Putri Catalya; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
Indonesia’s State-Owned Enterprise corporations nowadays are demanded to improve their internal control system effectiveness by creating a Good Corporate Governance as the result of the implementation of Keputusan Menteri BUMN Nomor 117 Tahun 2002. Therefore, many State-Owned Enterprise firms conducted ERP implementation into their business process as one of their information technology strategy. This study aims to analyze the effect of ERP systems implementation on the existence of internal control weaknesses over State-Owned Enterprise firms’ financial reporting in Indonesia. The samples of this research consisted of fifty four State-Owned Enterprise firms which had conducted operating business activities in 2010 and 2011, either have or have not announced implementation of ERP systems. Purposive sampling was used to select the control firms. Logistic regression was run by IBM SPSS software for data analysis and hypothesis examination, for instance Ogneva et al. (2007). Result of this study indicated that implementation of ERP systems contributes a positive influence, which is significant to the effectiveness of internal controls over State-Owned Enterprise firms’ financial reporting.